This time is different: Causes and consequences of British banking instability over the long run - Campbell, Gareth; Coyle, Christopher; Turner, John D. (Journal of Financial Stability, 2016)
This paper addresses three questions: (1) How severe were the episodes of banking instability experienced by the UK over the past two centuries? (2) What have been the macroeconomic indicators of UK banking instability? and (3) What have been the consequences of UK banking instability for the cost of credit? Using a unique dataset of bank share prices from 1830 to 2010 to assess the stability of the UK banking system, we find that banking instability has grown more severe since the 1970s. We also find that interest rates, inflation, lending growth, and equity prices are consistent macroeconomic indicators of UK banking instability over the long run. Furthermore, utilising a unique dataset of corporate-bond yields for the period 1860 to 2010, we find that there is a significant long-run relationship between banking instability and the credit-risk premium faced by businesses.